Analisis Prediksi dan Hubungan antara Debit Air dan Curah Hujan pada Sungai Ciliwung di Kota Bogor - Alfred Jansen Sutrisno; Kaswanto; Hadi Susilo Arifin (Graduate School Bogor Agricultural University (SPs IPB), 2020)
Water demand should be balance with water availability. The population of Bogor City was increased every year, so that water demand become increased. Currently, Government of Bogor City only utilizes the Cisadane river as a source for drinking water, but Bogor City has 2 rivers there are Cisadane river and Ciliwung river. So, Ciliwung river can be solution for this problem. Water discharge and rainfall influence water availability. Distribution log pearson type 3 used to predict the water discharge and rainfall and linier regression analyzed the relationship between water discharge (dependent variable) with rainfall as X1 and water level as X2 (independent variable). The result of distribution log pearson type 3 every return period 2, 5, 10, 25, dan 50 years is water discharge and rainfall were increased. Average increase of water discharge every return period is 1.6 m3/s and average increase of rainfall every return period is 251 mm. Partially, water discharge influenced by water level 97.7% and 2% by rainfall. But, = 0.000 < = 0.05. it is mean rainfall and water level cannot be ignored because it can influence water discharge with regression model = -3.01 + 0.000 X1 + 0.202 X2.